The strategically networked organization : leveraging social networks to improve organizational performance - Lehtimäki, Hanna (Emerald Group Publishing Limited, 2016)
This book demonstrates to managers the strategic significance of intra-organizational social networks. It argues that strategic management is embedded in the complexity of social relations that shape the strategic direction of a company. Currently there are few tools available to systematically collect information about the social functioning of an organization. This book fills this gap by shifting attention to the social relations that contribute to strategic advantage and that build on relationships that provide unique resources and create value for the business. It considers three perspectives on how social networks have a strategic function: first, social networks constitute everyday strategic action; second, social networks convey cultural meanings; and third, how social networks depict social processes that continually illustrate what the organization is and what it can become. The book shows top and upper-middle management how cultivating an understanding of intra-firm social relations can help them to build unique strategic advantage and make use of the day-to-day knowledge that emerges in the social connections and interactions within an organization.